Determinants of Purchasing Decisions with Developer Reputation and Location at Kharisma Cahaya Residence Housing - Windi Windi; Prasetyo Harisandi; Pipin Sukandi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to examine the influence of developer reputation and location as determining factors in home purchase decisions. The research was conducted at Kharisma Cahaya Residence, Bekasi. The method employed in this study is a quantitative approach, with the population consisting of consumers who have purchased houses at Kharisma Cahaya Residence, Bekasi. A total of 120 respondents were selected as the sample using a non-probability sampling technique to collect relevant data. Hypothesis testing was subsequently conducted using the SEM-PLS (Structural Equation Modeling-Partial Least Squares) analysis method. The results of the study indicate that developer reputation and location have a significant influence on property purchase decisions. A solid track record and extensive industry experience serve as a guarantee of trust for consumers. Meanwhile, strategic location serves as a key competitive factor influencing buyer preferences, as it relates to accessibility and long-term investment value. This study constructs a new model that integrates the theories of developer reputation, location, and purchase decisions. The uniqueness of this model lies in the comparison of current findings with previous research, as well as the use of primary data obtained from Kharisma Cahaya Residence, Bekasi. The research findings are expected to provide practical contributions to the property industry, particularly in urban fringe areas.